Improving the Availability of the Education Sector in Iraq over the Cloud Computing - Basi, Hussein (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Information and Communication Technology (ICT) start playing major rules in human life and specially in education sector. The education system is need to be redesign from the paper-based system to the digital-based system to fit the new era requirements. Cloud computing become an interesting technology according to their storages, distributions, web hosting, scalabilities and availabilities. The education system will take advantage from the cloud computing infrastructure to develop a flexible application to access and monitor the student’s information records as well as their lecturers within their institute to get required services over the teaching period. Adopting the education system to the cloud, will reduce the cost of managing, upgrading the infrastructure services. The e-education resources generate a high amount of data, as the student’s records need to be update during the study period by their lecturers regarding to their performance. The amount of data that are generated from each institute will be distributed according to their geographical location within the country to provide a close monitor to student’s records by the authorities. The goal of this study is to identify the interaction relationship among students, lecturers and administration staff. The interaction will be within the institute and among them by distributing the education data records over the cloud servers and allow a full admirative control to monitor the information for whatever update have been done to each record.